2015
DOI: 10.1002/cpa.21621
|View full text |Cite
|
Sign up to set email alerts
|

Convergence in Law of the Maximum of the Two‐Dimensional Discrete Gaussian Free Field

Abstract: We consider the discrete two-dimensional Gaussian free field on a box of side length N , with Dirichlet boundary data, and prove the convergence of the law of the centered maximum of the field.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
259
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2
1

Relationship

4
6

Authors

Journals

citations
Cited by 132 publications
(266 citation statements)
references
References 26 publications
6
259
0
1
Order By: Relevance
“…A key object for understanding their behavior is the derivative martingale studied here. Similar results have then been obtained for logarithmically correlated Gaussian fields such as the two-dimensional Gaussian Free Field: construction of the derivative martingale [37,38] and study of the extremes of these fields [62,27,36,20,21,19].…”
Section: Introductionsupporting
confidence: 68%
“…A key object for understanding their behavior is the derivative martingale studied here. Similar results have then been obtained for logarithmically correlated Gaussian fields such as the two-dimensional Gaussian Free Field: construction of the derivative martingale [37,38] and study of the extremes of these fields [62,27,36,20,21,19].…”
Section: Introductionsupporting
confidence: 68%
“…Log-correlated Gaussian fields are known to share many properties with BBM. For example, the distribution of the maximum [8,14,42], the overlap of extremal points [3,4,7], and their limiting Gibbs measures [48,51] behave similarly. It is therefore widely believed that their limiting extremal processes exist and should also exhibit the structure of Condition (SDP).…”
Section: If G Satisfies (21) Below Then (Sus) and (Sdp) Are Equivalmentioning
confidence: 81%
“…The most interesting and most subtle case is the critical one (d = 2 for the gradient model, d = 4 for the membrane model). For the gradient model, in a series of papers [BDG01, BDZ11, BZ12, BDZ16] it was shown that M ∇ N − m ∇ N converges in distribution to a randomly shifted Gumbel variable, where m ∇ N = 2 π log N − 3 √ 32π log log N . Even more is known, in particular convergence of the full extremal process [BL16,BL18].…”
Section: The Membrane Modelmentioning
confidence: 99%